2023
DOI: 10.1590/1980-220x-reeusp-2022-0394en
|View full text |Cite
|
Sign up to set email alerts
|

Spirituality, religiosity, and their representations for people living with HIV: daily life and its experiences

Abstract: Objective: To describe the process of living with HIV/AIDS in the daily life of people living with HIV in its interface with the social representations of spirituality and religiosity. Method: Qualitative research, supported by the theory of social representations. A semi-structured interview was carried out with 32 people undergoing treatment for HIV in an outpatient clinic specialized in HIV/AIDS. Analysis carried out with the support of software IRAMUTEQ. Results: Participants were mostly men, aged over 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 25 publications
0
0
1
Order By: Relevance
“…In our study, the majority of participants reported professing the Protestant religion (65.1%), Catholic (21.5%), Spiritist 0.3%, without religion (4.8%), and others (8.2%). In contrast to the results of our research, Nogueira et al (15) in their study with 160 HIV-positive participants, in terms of religion, 38% of the interviewees declared themselves Catholic, 25.3% were Spiritist/Spiritualist, 19.3% were of evangelical origin, and 17.5% reported having no religion. Furthermore, Santos (16) states that historically, spirituality and religion have been considered important determinants of health, as their values and systems in uence individuals' formation, bring ful llment and stability to their lives, among other positive associations of spirituality and religiosity.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, the majority of participants reported professing the Protestant religion (65.1%), Catholic (21.5%), Spiritist 0.3%, without religion (4.8%), and others (8.2%). In contrast to the results of our research, Nogueira et al (15) in their study with 160 HIV-positive participants, in terms of religion, 38% of the interviewees declared themselves Catholic, 25.3% were Spiritist/Spiritualist, 19.3% were of evangelical origin, and 17.5% reported having no religion. Furthermore, Santos (16) states that historically, spirituality and religion have been considered important determinants of health, as their values and systems in uence individuals' formation, bring ful llment and stability to their lives, among other positive associations of spirituality and religiosity.…”
Section: Discussioncontrasting
confidence: 99%
“…Para os entrevistados, a prática de espiritualidade/religião/religiosidade esteve além da frequência em instituições religiosas, presente também no bem que realizam a outrem e nos rituais que consideram sagrados. À vista disso, o sentido religioso/espiritual, tanto quanto suas práticas inerentes ou não à sua essência, puderam propiciar saúde física ou mental favoráveis(NOGUEIRA et al, 2023b).No tocante a influência da espiritualidade/religião/religiosidade, foi percebido o quanto favorecem o autofortalecimento mediante o enfrentamento do viver com HIV(NOGUEIRA et al, 2023b) e a compreensão do processo saúde-doença, que disponibilizou menor intensidade do sofrimento(DOMINGUES et al, 2020).Nesse sentido, recorrer à uma divindade e à fé pôde dar a sensação de capacidade(NOGUEIRA et al, 2023a). Relativamente, à influência positiva,Santos, et al (2020) trouxeram que a espiritualidade é fator ímpar no comportamento da PVHIV; seja no tratamento ou vivendo com o vírus, a fé é grande auxiliadora frente aos desafios, com diferentes aspectos no campo da espiritualidade(NOGUEIRA et al, 2019).…”
unclassified